Factors affecting pretransplant muscle strength in allogeneic stem cell transplant candidates prior transplantation - Limbach, Matthias; Kühl, Rea; Köppel, Maximilian; Dreger, Peter; Luft, Thomas; Bohus, Martin; Wiskemann, Joachim (Supportive care in cancer, 2025)
Purpose Physical performance is crucial for prognosis after allogeneic hematopoietic stem cell transplantation (allo-HCT). Cardiorespiratory fitness has already been shown to have prognostic value, and there is increasing evidence that muscle strength and associated parameters (e.g., sarcopenia) are also of clinical relevance. Therefore, there is a need for the quantification of muscle strength and defining risk factors for reduced performance values. Methods Maximal voluntary isokinetic (MVIC) and isometric (MIPT) muscle strength was assessed 2.4 ± 7.1 days prior admission for allo-HCT with a stationary isokinetic testing machine (IsoMed2000). We calculated percentiles for knee extension and hip flexion using healthy reference values. Regression models were used to identify predictors for reduced muscle strength including gender, age, body mass index (BMI), number of previous cardiotoxic therapies, number of previous transplantations, comorbidity index (HCT-CI), hemoglobin level, and physical activity. Results Data of 212 patients (male n = 143, female n = 69), with a mean age of 54.49 ± 11.4, revealed considerably deviations from healthy reference values. Patients were located in the following percentiles: MVICKnee 37.5 ± 30.3, MVICHip 39.5 ± 31.3 and MIPTKnee 22.9 ± 26.5; MIPTHip 22.6 ± 27.4. Sub-group analyses showed that patients with younger age and male gender possess the highest deviations. Muscle strength values were significantly (p < 0.05) influenced by age, female gender, lower BMI, and higher HCT-CI. Conclusion Muscle strength is considerably reduced immediately prior to allo-HCT. Identified patient characteristics for reduced muscle strength point to the population that should be primarily targeted with exercise respectively resistance training interventions prior to allo-HCT to contribute to a well prepared transplant candidate. Trial registration NCT01374399.
Online veröffentlicht: 10. Januar 2025
Gesehen am 15.07.2025